Delay in ship berthing / Muhamad Rizal Sawal - Sawal, Muhamad Rizal (1995)
Delay in ship berthing at Port Klang has become a serious problem in our shipping industry. The objective of this study are to determine the level of delay that is faced by Mitsui O.S.K lines Ltd container ships and also to identify the factors that cause the existing problem.